Plasma and Intracellular Pharmacokinetics of Tenofovir Disoproxil Fumarate 300 mg Every 48 Hours vs 150 mg Once Daily in HIV-Infected Adults with Moderate Renal Function Impairment - Tim R. Cressey (2018)
© 2015 The Author 2015. Background. The approved tenofovir disoproxil fumarate (TDF) dose of 300 mg every 48 hours for adults with moderate renal impairment is often confusing and inconvenient. Using a new TDF formulation, we compared the pharmacokinetics of the standard dose with a dose of 150 mg once daily in HIV-infected adults. Methods. This was an open-label pharmacokinetic study. Virologically suppressed HIV-infected adults with a creatinine clearance 30 to < 50 mL/minute receiving TDF 300 mg every 48 hours as part of a nonnucleoside reverse transcriptase inhibitor (NNRTI)- or lopinavir/ritonavir (LPV/r)-based regimen were enrolled. Intensive 48-hour blood sampling for pharmacokinetic assessment was performed at enrollment, after which the TDF dose was changed to 150 mg once daily. Two weeks later, 24-hour blood sampling was performed; subjects then returned to the standard dose. Tenofovir (TFV) pharmacokinetic parameters were calculated using a noncompartmental analysis. Results. Forty adults (55% female) were enrolled: 20 receiving NNRTI-based and 20 receiving LPV/r-based treatment. Median age was 56 years (range, 44-65 years), weight 51 kg (range, 38-80 kg), and creatinine clearance 43.9 mL/minute (range, 30.9-49.7 mL/minute). The TFV geometric mean ratio of the area under the curve (AUC < inf > 0-48h < /inf > ) for every 24 hours vs every 48 hours was 1.09 (90% confidence interval [CI],. 98-1.22) and 1.00 (90% CI,. 92-1.09) for patients receiving NNRTI- and LPV/r-based treatment, respectively. Concomitant LPV/r use markedly increased TFV plasma concentrations, and AUC < inf > 0-48h < /inf > was 67% higher with the standard dose, whereas no differences in intracellular TFV diphosphate concentrations were observed. All subjects remained virologically suppressed, and no drug-related adverse events were reported. Conclusions. TDF 150 mg every 24 hours provides comparable systemic exposure to the standard dose of 300 mg every 48 hours in patients with moderate renal impairment.